Effects of Alumina Micro-Powder Additions on Properties of Special Silicon Mullite Brick - Liu, Zhenying; Feng, Desheng; Wang, Jing (Asian Journal of Chemistry, 2013)
Special silicon mullite brick for transition belt of cement kiln was prepared using bauxite clinke, white fused alumina, silicon carbide, guangxi white clay, alumina micro-powder additions as main starting materials and sulfite pulp waste liquid as binder. Effects of alumina micropowder additions on cold physical properties, thermal shock resistance and abrasion resistance of silicon mullite brick were studied. The samples were characterized by XRD and SEM. The results showed that with alumina micro-powder addition increasing, cold strength, bulk density of special silicon mullite brick were first enhanced and then declined; apparent porosity first decreased and then increased; thermal shock resistance of the brick was first enhanced and then declined. When the addition of alumina micro-powder was 4 %, the silicon mullite brick had the best properties and the brick as ideal lining materials of the transition belt of large-scale cement rotary kiln.